Pemidanaan terhadap Anak sebagai Pelaku Tindak Pidana Terorisme - Hengky Prasetyo; Kadek Wiwik Indrayanti (MLJ Merdeka Law Journal, 2022)
This study aims to examine the criminalization of children as perpetrators of terrorism and the appropriate criminal sanctions against children as perpetrators of terrorism. This study uses normative legal research method because it examines and analyzes the criminalization of children as perpetrators of terrorism and the regulation of sanctions. The result of the study is that a child involved in terrorism network receives special protection from the state based on the mandate of UUPA considering that the child as a perpetrator of terrorism is actually a victim of the terrorism network itself. Regarding Child Perpetrators of Terrorism crimes, the SPPA Law has not regulated the handling of Child Perpetrators of terrorism. However, children are still children who must be protected and fulfill all their rights. The concept of criminal responsibility applied to adults cannot be applied to children as perpetrators of terrorism, as stipulated in Law No. 11/2012 on Juvenile Justice System.DOI: https://doi.org/10.26905/mlj.v3i2.9214